PAH–DNA Adducts in Cord Blood and Fetal and Child Development in a Chinese Cohort - Tang, Deliang (National Institute of Environmental Health Sciences, 2006)
Polycyclic aromatic hydrocarbons (PAHs) are an important class of toxic pollutants released by fossil fuel combustion. Other pollutants include metals and particulate matter. PAH–DNA adducts, or benzo[a]pyrene (BaP) adducts as their proxy, provide a chemical-specific measure of individual biologically effective doses that have been associated with increased risk of cancer and adverse birth outcomes. In the present study we examined the relationship between prenatal PAH exposure and fetal and child growth and development in Tongliang, China, where a seasonally operated coal-fired power plant was the major pollution source. In a cohort of 150 nonsmoking women and their newborns enrolled between 4 March 2002 and 19 June 2002, BaP–DNA adducts were measured in maternal and umbilical cord blood obtained at delivery. The number of gestational months occurring during the period of power plant operation provided a second, more general measure of exposure to plant emissions, in terms of duration. High PAH–DNA adduct levels (above the median of detectable adduct level) were associated with decreased birth head circumference (p = 0.057) and reduced children’s weight at 18 months, 24 months, and 30 months of age (p < 0.05), after controlling for potential confounders. In addition, in separate models, longer duration of prenatal exposure was associated with reduced birth length (p = 0.033) and reduced children’s height at 18 (p = 0.001), 24 (p < 0.001), and 30 months of age (p < 0.001). The findings suggest that exposure to elevated levels of PAHs, with the Tongliang power plant being a significant source, is associated with reduced fetal and child growth in this population.